The Impact of Action Effects on Infants’ Predictive Gaze Shifts for a Non-Human Grasping Action at 7, 11, and 18 Months - Adam, Maurits; Gumbsch, Christian; Butz, Martin V.; Elsner, Birgit (Frontiers in Psychology, 2021)
During the observation of goal-directed actions, infants usually predict the goal at an earlier age when the agent is familiar (e.g., human hand) compared to unfamiliar (e.g., mechanical claw). These findings implicate a crucial role of the developing agentive self for infants’ processing of others’ action goals. Recent theoretical accounts suggest that predictive gaze behavior relies on an interplay between infants’ agentive experience (top-down processes) and perceptual information about the agent and the action-event (bottom-up information; e.g., agency cues). The present study examined 7-, 11-, and 18-month-old infants’ predictive gaze behavior for a grasping action performed by an unfamiliar tool, depending on infants’ age-related action knowledge about tool-use and the display of the agency cue of producing a salient action effect. The results are in line with the notion of a systematic interplay between experience-based top-down processes and cue-based bottom-up information: Regardless of the salient action effect, predictive gaze shifts did not occur in the 7-month-olds (least experienced age group), but did occur in the 18-month-olds (most experienced age group). In the 11-month-olds, however, predictive gaze shifts occurred only when a salient action effect was presented. This sheds new light on how the developing agentive self, in interplay with available agency cues, supports infants’ action-goal prediction also for observed tool-use actions.